Pemahaman Masyarakat Sadar Hukum Membayar Zakat Hasil Usaha - Januardi, Hengki; Yulius, Yulius; Wahida, Hasanatul (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
which is a concern for the weak. Zakat is paid by a muzakki given to the mustahik. In this study, it appears that the understanding of people of Lengayang District only understands the zakat fitrah that they pay during the fasting month. For the measure of payment, they only estimate it. In the efforts that must be made so that people's understanding of the obligation of zakat can be achieved through coaching muzakki and mustahiq, of course, there is good cooperation between all parties involved, namely the community itself, the Zakat Collection Unit, village officials, religious scholars, and religious extension workers are no exception. Islam. The implementation of zakat in Lengayang District is marked by the presence of supporting and inhibiting factors as well as efforts to build public awareness of paying zakat. This is inseparable from the role of the Lengayang District Office of Religious Affairs under the auspices of the Ministry of Religion as Amil Zakat Trustees who have carried out program development by establishing a zakat consulting institution in order to increase awareness of zakat for the community. Keywords: Understanding, Legal Awareness, Zakat Results of Business.